ROLE GOVERNMENT AREA IN PLANNING DEVELOPMENT AREA IN THE MANATUTO DISTRICT OF TIMOR LESTE - Ika Widiastuti; Anisa Pramitasari (Perkumpulan Dosen Program Hibah Indonesia, 2023)
Role government area in planning development area that is own authority and ability to manage, implementing regional development programs. Government _ area determine success process implementation government and development activities in the region. P rocess of regional development planning in the District Manatuto, Timor Leste plan started from community public, village, board village, subdistrict And stakeholders in the region. Reviewed policies from the central government to approve plan documents the area The community is not satisfied, because the regional development plan document was ratified by the central government is not based on the plan document submitted to the central government. The aim of this research is to: a) describe and analyze the role of regional government as Entrepreneur, Coordinator, facilitator And Stimulators in planning development in district Manatuto. b) describe and analyze the supporting and inhibiting factors of the government's role areas in regional development planning in the Manatuto district. The method used is descriptive qualitative. Results study that is local government as Entrepreneur, Coordinator, facilitator and Stimulator to participate in the team Regional Development Commission to verify, evaluate and supervise the program priority planning development area